Immunization programs for hospital healthcare workers in Northern-Italy, can we do more?. (30th September 2020) - Antinolfi, F; Brunelli, L; Malacarne, F; Cocconi, R; Brusaferro, S
Abstract: Background: Coverage for vaccine-preventable diseases (VPDs) among healthcare workers (HCWs) in Italy remains low, and WHO strongly recommends to tailor immunization programs to tackle hesitancy. Aim of the study was to investigate HCW-specific immunization programs within Friuli Venezia Giulia (FVG) Region in order to plan new common strategies. Methods: In December 2019 we collected information about FVG hospitals and HCWs immunization programs conducted within each of them, including: number of HCWs employed, monitored VPDs, immunization assumption, vaccination strategies and refusers management. Results: We obtained data from 7/7 hospitals, for a total of 12, 557 employed HCWs (average 1, 794; range 467-3, 922); 2 hospitals are academic centers, while 2 are research institutions. All hospitals have immunization programs for measles, mumps, rubella; the majority for hepatitis B (6/7); 5 for diphtheria, tetanus, pertussis, chicken pox. Presumptive evidence of immunity is established when written vaccination documentation is available or in presence of laboratory evidence. HCWs immunization programs are responsibility of the occupational doctor in most hospitals (6/7). Vaccination promotion strategies include: mail or email personal invitation, training courses, video and notice display on hospital website, reminders. Most hospitals set up a dedicated vaccination service located in a hospital common area (4) or outside the hospital (2); one hospital also offered ward on-site vaccination. For airborne or droplets transmission diseases, refusers are asked to wear a mask during shift in 2 hospitals. Conclusions: HCWs immunization programs in FVG Region are heterogeneous, and their specific effectiveness has to be studied yet. This study represents the first step in the process of FVG hospitals engagement in sharing effective actions in order to plan a new regional strategy for HWCs immunization. Key messages: The investigation of effective strategies conducted in different FVG hospitals is essential for their scaling-up evaluation. A common regional plan for healthcare workers immunization is needed to tackle hesitancy and reduce infectious risk within hospitals.